Impact on Stakeholders in a Changing Arctic Oil and Gas Development in the Russian Arctic - Valeeva, Vilena; Keil, Kathrin; Gabriel, Johannes; Nikitina, Elena (Zenodo, 2017)
•Changes in the Arctic strongly affect ecosystems, people and business both inside the Arctic and at lower latitudes. •We need a better understanding of the interplay between regional and global systems (meteorological, climatic, economic, technological, legal, political) within the Arctic and their impacts beyond the region. •We conduct a study of the impact of Arctic changes on business - specifically resource development - in the Arctic with the purpose of improving stakeholders’ capacity to adapt to climate change. Poster presented at the Conference 2017 International Conference on Arctic Science: Bringing Knowledge to Action n (AMAP) http://www.amap.no/about The 2017 International Conference on Arctic Science: Bringing Knowledge to Action will: Bring together diverse expert communities ranging from scientists to decision-makers in order to identify, explore and create mechanisms and venues where science and knowledge can inform the development of policies and decision-making. We support the Blue Growth! Visit us on: www.blue-action.eu Follow us on Twitter: @BG10Blueaction